Exploring changes in guest preferences for Airbnb accommodation with different levels of sharing and prices: using structural topic model - Ding, Kai; Choo, Wei Chong; Ng, Keng Yap; Zhang, Qing (Frontiers Media, 2023)
Introduction: Online reviews have become an important source of information for investigating customers’ consumption experiences in academic studies. In the context of sharing economy-based accommodation, various studies have been conducted to investigate the user experience of Airbnb by analyzing online reviews; however, most previous Airbnb studies had focused on analyzing the user experience of Airbnb at a holistic level without distinguishing the accommodation attributes of Airbnb. Therefore, this article aimed to investigate how the preferences revealed by Airbnb users in online reviews vary across Airbnb listings with different levels of sharing and price ranges.